ANALISIS BEBAN KERJA MENTAL PEKERJA BAGIAN GROUND H ANDLING BANDARA ADISUTJIPTO UNTUK MENDUKUNG KESELAMATAN PENERBANGAN - Poerwanto, Eko; Gunawan, Gunawan (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Increased need for air transport will increase the activity of ground handling at airports. Increased activity of this will affect the mental workload received personnel who carry it out. Any increase in mental workload will affect the occurrence of human error and affect flight safety. Analysis of mental workload ofpart o f ground handling personnel is very important to ensure acceptable personnel workloads according to workload capacity available. This mental workload research using NASA-TLX method, that the procedure uses a multi-dimensional rating, and divide the workload on the basis of the average loading 6 dimensions, namely Mental Demand, Physical Demand, Temporal Demand, Effort, Own Performance, and frustation. NASA-TLX is divided into two phases, namely a comparison of each scale (Paired Comparison) and giving value to the work (Event Scoring). The research objective is to ensure the mental workload of part of ground handling Adisucipto airport in Yogyakarta, in accordance with their capacity, so as to avoid human error and to support aviation safety. The results showed that the mean score of mental workload ground handling activities by PT. Gapura Air and PT. Kokapura Avia in Yogyakarta Adisucipto airport in the mental workload optimization group, which indicates mental workload received by workers are safe (no overload).